ASIMILASI DALAM ISOLEK BONAI ULAKPATIAN - Zainal Abidin (Balai Bahasa Provinsi Riau, 2016)
This study aims at describing the assimilation of Bonai Ulakpatian isolect in RiauProvince. This study is a linguistics research about sound changing that occurs on the different sounds to be the same sounds at the position between two vowels in the middle of a word in an isolect that is used by Bonai ethnic group in Ulakpatian Village, Rokan Hulu Regency. The data of the research is the utterances data of Bonai ethnic group community that referred to in selection of language data. The data were collected by applying interview method by using conversation and recording technique. The data were described phonetically by using IPA symbol, the data were compared with PM and made conclusion The result of the research shows that Bonai Ulakpatian isolect has four assimilation forms at the position between two vowels in the middle of a word, namely 1) PM *nd/v-v> BU [n]/v-v, 2) PM *ŋg/v-v> BU [ŋ]/v-v, 3) PM *mb/v-v> BU [m]/v-v that are total progressive assimilation and phonetics assimilation, and 4) PM *nj/v-v> BU [ñ]/v-v that are reciprocal and phonemic assimilation.